Laws and Emerging Technologies - Esther Salmerón-Manzano (Laws, 2021)
New technologies and so-called communication and information technologies are transforming our society, the way in which we relate to each other, and the way we understand the world. By a wider extension, they are also influencing the world of law. That is why technologies will have a huge impact on society in the coming years and will bring new challenges and legal challenges to the legal sector worldwide. On the other hand, the new communications era also brings many new legal issues such as those derived from e-commerce and payment services, intellectual property, or the problems derived from the use of new technologies by young people. This will undoubtedly affect the development, evolution, and understanding of law. This Special Issue has become this window into the new challenges of law in relation to new technologies.